“Traurige Rückwanderung der Brasilianer nach ihrem jüngst verlassenen Vaterlande” – Ein Gedicht zum Thema Auswanderung nach Brasilien - Neumann, Gerson (Contingentia, 2009)
German immigration to Brazil starts in the 19th century. In Brazil, the Literature of German Immigrants has been the subject of many studies. On the other hand, the literary production on immigration to Brazil, produced in Germany during this period, is still quite unknown. This article will discuss one specific poem in this context, a text from 1847 called Traurige Rückwanderung der Brasilianer nach ihrem jüngst verlassenen Vaterlande.